A Tree Peony Trihelix Transcription Factor PrASIL1 Represses Seed Oil Accumulation - Yang, Weizong; Hu, Jiayuan; Behera, Jyoti R.; Kilaru, Aruna; Yuan, Yanping; Zhai, Yuhui; Xu, Yanfeng; Xie, Lihang; Zhang, Yanlong; Zhang, Qingyu; Niu, Lixin (Frontiers in Plant Science, 2021)
In many higher plants, seed oil accumulation is governed by complex multilevel regulatory networks including transcriptional regulation, primarily affects fatty acid biosynthesis. Tree peony (Paeonia rockii), a perennial deciduous shrub endemic to China is notable for its seed oil that is abundant in unsaturated fatty acids. We discovered that a tree peony trihelix transcription factor, PrASIL1, localized in the nucleus, is expressed predominantly in developing seeds during maturation. Ectopic overexpression of PrASIL1 in Nicotiana benthamiana leaf tissue and Arabidopsis thaliana seeds significantly reduced total fatty acids and several major fatty acid compositions. These changes were in turn associated with the decreased expression of multitudinous genes involved in plastidial fatty acid synthesis and oil accumulation. Thus, we inferred that PrASIL1 is a critical transcription factor that represses oil accumulation by down-regulating numerous key genes during seed oil biosynthesis. In contrary, up-regulation of oil biosynthesis genes and a significant increase in total lipids and several major fatty acids were observed in PrASIL1-silenced tree peony leaves. Together, these results provide insights into the role of trihelix transcription factor PrASIL1 in controlling seed oil accumulation. PrASIL1 can be targeted potentially for oil enhancement in tree peony and other crops through gene manipulation.